619 HIGH DISCOVERY RATE OF GASTRODUODENAL EOSINOPHILIA BUT NOT EOSINOPHILIC ESOPHAGITIS IN PATIENTS WITH CHRONIC GASTROINTESTINAL SYMPTOMS. (17th September 2021) - Talley, Nicholas; Kamboj, Amol; Chey, William; Rasmussen, Henrik; Lacy, Brian; Hirano, Ikuo; Chehade, Mirna; Gonsalves, Nirmala; Peterson, Kathryn; Lembo, Anthony; Schmitt, Colleen; Rothenberg, Marc; et al.
Abstract:  : Although the prevalence of eosinophilic gastrointestinal disorders (EGIDs) is increasing, there is evidence that eosinophilic gastritis and/or duodenitis (EG/EoD) are underdiagnosed. Patients with EG/EoD often present with chronic, non-specific gastrointestinal (GI) symptoms, similar to patients with functional GI disorders. We hypothesized that systematic evaluation, including multiple esophageal, gastric and duodenal biopsies, of patients with chronic GI symptoms might reveal a high rate of gastroduodenal eosinophila, with or without eosinophilic esophagitis (EoE). Methods: We performed a prospective multi-center study of patients with non-specific GI symptoms for ≥6 months, from 20 sites. Patients completed a questionnaire assessing abdominal pain, abdominal cramping, early satiety, bloating, nausea, vomiting, diarrhea, and loss of appetite. Those with daily average symptom severity scores ≥3/10 for any single symptom underwent esophagogastroduodenoscopy (EGD) with collection of 4 esophageal (EoE), 8 gastric, and 4 duodenal biopsies, analyzed by central pathologists. Histologic criteria for EoE was ≥15eos/hpf in ≥1 esophageal site and for EG/EoD was peak eosinophil counts ≥30/hpf in ≥5 gastric hpfs and/or 3 duodenal hpfs—criteria used in randomized trials. Results: Of 556 patients screened, 405 (73%) met symptom criteria and underwent EGD; 181 patients (45%, mean age 45, 73% female) who underwent EGD met the histologic criteria for EG/EoD, and of these, 7% also had EoE diagnosed. Overall 2% met histologic criteria for EoE alone. Of patients who met the histologic criteria for EG/EoD, 93% were previously diagnosed with gastroesophageal reflux disease (GERD), irritable bowel syndrome (IBS), or functional dyspepsia (FD) (Figure 1). The average duration of GI symptoms in the screened population as well as those that met histologic criteria for EG/EoD was 11 years. Conclusion: Forty-five percent of patients with moderate-to-severe GI symptoms who underwent EGD met histologic criteria for EG/EoD. Over 90% of these patients had previously been diagnosed with GERD, IBS, and/or FD, and had minimal overlap with EoE. EGD with systematic gastroduodenal biopsies, and intentional evaluation for tissue eosinophilia, should be performed in patients with chronic GI symptoms. Accurate diagnosis of EG/EoD is required for appropriate, targeted treatment and improved outcomes of patients with moderate-to-severe GI symptoms.